KEMAMPUAN PENGGUNAAN JOSHI –KARA DAN -MADE SISWA KELAS X SMA PGRI 2 PADANG - Joni Kurniawan; Hendri Zalman; Damai Yani (Universitas Negeri Padang, 2018)
Abstract The purpose of this research is to knowing ability of student of class X at SMA PGRI 2 padang about using joshi –kara and –made in sentence. Kind of this research is kuantitatif research, with descriptive method. Populasion in this research is students of class X at SMA PGRI 2 Padang. Total population is 165 students. using random sampling technic to choosed the sample, that 28 students of class X1. This research use the testing instrument, that double selection test and sentence compliting test. The goal of this research is how ability of students of class X at SMA PGRI 2 padang about using joshi –kara and –made in sentence. Crop of this research is ability of students of class X at SMA PGRI 2 padang about joshi –kara is better than using joshi –made or joshi –kara and –made, becausing students know about using the word before joshi –kara and the function in great sentence. In the other way, students ability is low in using joshi –made. Because, students less in understanding to using joshi –made in great sentence gramaticaly. Student highest result of rank in identify indicator of joshi –kara, -made or –kara and –made in sentence is 100, with lowest rank 33. And average rank is 67,3. In using indicator of joshi –kara, -made or –kara and –made, the highest rank is 100, the lowest rank 20. And average is 65,0 Keywords: ability, joshi, kara,made